PENDAMPINGAN PENYUSUNAN PERANGKAT PEMBELAJARAN BERBANTUKAN ALAT PERAGA TERINTEGRASI APLIKASI TRACKER BERBASIS TEKNOLOGI SENSOR DI SEKOLAH BINAAN SMKS ASY’ARIYYAH DAN SMPS ISLAM ASY’ARIYYAH - Jufrida Jufrida; Rahma Dani; M. Furqon (Universitas Muhammadiyah Mataram, 2023)
ABSTRAKDi era Pendidikan 4.0 saat ini, diperlukan inovasi dalam perancangan dan pelaksanaan percobaan fisika yang terintegrasi dengan teknologi agar pembelajaran dapat berjalan dengan lebih efektif dan menarik bagi siswa. Namun masih ditemukan sejumlah sekolah khususnya di Kabupaten Muaro Jambi yang menggunakan merancang dan melaksanakan percobaan secara konvensional serta belum memanfaatkan teknologi, seperti SMKS Asy’ariyyah dan SMPS Islam Asy’ariyyah Muaro Jambi. Tujuan pengabdian masyarakat ini adalah memberikan pendampingan kepada guru-guru di kedua sekolah tersebut dalam menyusun perangkat pembelajaran fisika berbantukan alat peraga terintegrasi aplikasi Tracker dan teknologi sensor. Metode yang digunakan dalam kegiatan ini adalah workshop yang terdiri dari tiga tahapan, yaitu persiapan Kegiatan ini dilaksanakan pada tanggal 16 Agustus 2022 dan hari kedua tanggal 20 Agustus 2022. Setelah melakukan kegiatan pelatihan pembuatan perangkat pembelajaran terintegrasi aplikasi Tracker dan teknologi sensor, guru- guru SMPS Islam Asy’Ariyyah dan SMKS Islam Asy’Ariyyah sudah terlatih dalam membuat perangkat pembelajaran terintegrasi aplikasi Tracker dan teknologi sensor. Kata kunci: alat peraga; perangkat pembelajaran; sensor; tracker. ABSTRACTDuring the covid 19 pandemic and plus the new variant of the omicron virus, learning is still carried out online in order to avoid covid 19, to anticipate that experiments in class can be carried out properly, a learning tool must be designed using props integrated with a tracker application based on sensor technology. During the Covid-19 pandemic, teachers and students are required to implement health protocols in learning, teachers are required to develop learning tools in the classroom. Digital-based science learning has not been widely applied in schools. Teachers still have difficulty developing learning tools assisted by props integrated with sensor technology-based tracker applications. The method used in this activity is demonstration, counseling, discussion, training and practice delivered by the service team to teachers of Asy'Ariyyah Islamic Junior High School and Asy'Ariyyah Vocational School, this activity was carried out on August 16, 2022 and the second day on August 20, 202. Service activities are very much needed for schools, with this service activity teachers are motivated and there is additional insight in teaching integrated learning devices for tracker applications and sensor technology and getting inspiration for teachers to make integrated learning devices for tracker applications and sensor technology. After conducting training activities for making integrated learning devices for tracker applications and sensor technology, Asy'Ariyyah Islamic Junior High School teachers, Asy'Ariyyah Islamic Vocational High School have been trained in making integrated learning devices for tracker applications and sensor technology. The need for creative and innovative learning media in order to create a pleasant learning atmosphere. Keywords: learning device; sensor; tracker; teaching aid.